Pharmacologically induced amnesia for learned fear is time and sleep dependent - Merel Kindt (Nature Portfolio, 2018)
Emotional memory can change when retrieved, yet the conditions under which this can occur are not fully described. Here, authors show that taking a pill of propranolol taken during a specific time window can change the expression of fear memory in a person, and that sleep is necessary to forget learned fear.